2019
DOI: 10.1016/j.seizure.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Optimized SEEG-guided radiofrequency thermocoagulation for mesial temporal lobe epilepsy with hippocampal sclerosis

Abstract: Concerns about the impact of open surgery for drug-resistant mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS) have driven interest in minimally invasive techniques. Stereo-electro-encephalography guided radiofrequency thermocoagulation (SEEG guided RF-TC) offers an alternative choice but with currently limited efficacy. We developed a procedure for optimally extended thermocoagulative lesions and investigated the efficacy and safety for MTLE-HS in a preliminary observational study. Methods: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…A contiguous bipolar RF-TC using one electrode was considered to be one-dimensional, while RF-TC using coupling contacts from two electrodes in one plane was two-dimensional. Three-dimensional cross-bonding of various electrode contacts provided a novel method to optimize SEEG-guided RF-TC ( 24 ). Through this process, the scope of thermal coagulation was expanded.…”
Section: Methodsmentioning
confidence: 99%
“…A contiguous bipolar RF-TC using one electrode was considered to be one-dimensional, while RF-TC using coupling contacts from two electrodes in one plane was two-dimensional. Three-dimensional cross-bonding of various electrode contacts provided a novel method to optimize SEEG-guided RF-TC ( 24 ). Through this process, the scope of thermal coagulation was expanded.…”
Section: Methodsmentioning
confidence: 99%
“…SEEG is considered the “gold standard” method to evaluate the epileptogenic zones for electrodes implanted in the deep brain and can record interictal and ictal epileptic discharges for days before deciding the extent of resection [ 6 , 7 , 8 , 9 ]. Our team at the China International Neuroscience Institute (China-INI) of XuanWu Hospital has also confirmed the value of SEEG in the assessment and guidance of thermocoagulation of epileptogenic foci [ 10 ].…”
Section: Introductionmentioning
confidence: 92%
“…Should the lesioning field be expanded by integrating multiple contacts to coagulate in a network manner, that is, stereo-crossed RF-TC (scRF-TC)? After preliminary albumen and animal investigations, 12 our recent studies have shown that, with this design, seizure outcomes in patients with hypothalamic hamartomas and hippocampal sclerosis were improved without a secondary craniotomy. 8,12 To further quantify the characteristics of scRF-TC that are important to the clinical practice from bed to the bench, it is necessary to address the constraints of albumen as a liquid.…”
Section: Introductionmentioning
confidence: 99%
“…After preliminary albumen and animal investigations, 12 our recent studies have shown that, with this design, seizure outcomes in patients with hypothalamic hamartomas and hippocampal sclerosis were improved without a secondary craniotomy. 8,12 To further quantify the characteristics of scRF-TC that are important to the clinical practice from bed to the bench, it is necessary to address the constraints of albumen as a liquid. Specifically, in the scRF-TC, if the configurations and distances of the deformable electrodes are to be calibrated by holding the electrodes more stably, a semi-solid phantom would be better.…”
Section: Introductionmentioning
confidence: 99%